Assessment of social emotional, cognitive and communicative development and adaptive behavior in children with spinal muscular atrophy 5q - Yu. O. Papina; N. N. Zavadenko; E. A. Melnik; S. B. Artemyeva; I. A. Berdalina; D. V. Vlodavets (Нервно-мышечные болезни, 2025)
Background. Spinal muscular atrophy 5q (SMA) is a severe genetic neuromuscular disorder, which is primarily manifested through musclar weakness. Previously, cognitive development in the natural course of SMA was considered normal. The introduction of etiopathogenetic therapy has altered the disease trajectory, led to new phenotypes, improved survival rates, and outlined the importance of studying the development of emotional, cognitive, and communicative domains, and adaptive behavior in SMA patients.Aim. To conduct a comprehensive assessment of emotional, cognitive, and adaptive domains, as well as speech development, in patients with genetically confirmed SMA, including cases, which were identified through newborn screening programs and were asymptomatic at the initiation of etiopathogenetic therapy, and to identify factors influencing neuropsychic development in SMA patients.Materials and methods. The study included 87 SMA patients receiving etiopathogenetic therapy, aged 0–12 years (median age at testing – 57.0 [37.0; 103.0] months). The Developmental Profile-3 (DP-3) instrument was used to assess neuropsychic development. Statistical analysis was performed using SPSS Statistics v.26.0 (IBM, USA).Results. Children who received therapy at the presymptomatic stage (6.9 % of the cohort) showed no deficits in any assessed developmental domains. These results significantly differed from those of SMA types 1, 2, and 3 in motor skills (padj <0.001) and adaptive behavior (padj ≤0.026). Patients with SMA types 1, 2, and 3 exhibited severe motor impairments (reduced motor skills in 93.0 %, 89.7 %, and 88.9 % of children, respectively) and adaptive deficits (impairments in ≥55 % of each group). SMA type 1 patients additionally demonstrated delays in social emotional (39.5 %), cognitive (30.2 %), and communicative (39.5 %) domains. Children with lower functional status (“lying”) had more pronounced delays in adaptive, social emotional, and cognitive domains (p ≤0.048). In SMA type 1, fewer SMN2 gene copies and earlier disease onset correlated with more severe deficits in emotional, cognitive, and adaptive domains, as well as in speech development (SMN2 copies: p ≤0.034; age of onset: p ≤0.012). SMA type 1 patients with dysphagia showed lower scores across all subscales except motor skills (p ≤0.015). Chronic respiratory insufficiency was associated with reduced scores in all five subscales: in SMA type 1, motor skills, adaptive, social emotional, and cognitive domains were affected (p ≤0.045); in SMA type 2, adaptive, social emotional, and cognitive domains were affected (p ≤0.018). Delayed therapy initiation correlated with lower motor and adaptive scores in SMA types 1 (p ≤0.012), 2 (p ≤0.002), and 3 (p ≤0.048), and with worse social emotional and cognitive outcomes in SMA type 2 (p = 0.001).Conclusion. SMA patients exhibit not only motor impairments but also adaptive and socialization deficits, as well as delays in communicative and cognitive development. A standardized approach to identifying these impairments should be developed, and developing tailored rehabilitation methods is important as well. Initiating etiopathogenetic therapy at the presymptomatic stage may prevent neuropsychiatric manifestations of SMA.